A good mix against ultra-poverty? Evidence from a Randomized Controlled Trial (RCT) in Bangladesh - Rahman, Atiya; Bhattacharjee, Anindita; Das, Narayan (Wiley Online Library, 2022)
This article was published in Review of Development Economics [©2021 Published by John Wiley & Sons Ltd] and the definite version is available at: https://doi.org/10.1111/rode.12809 The Article's website is at: https://onlinelibrary.wiley.com/doi/10.1111/rode.12809